2017
DOI: 10.1590/0103-8478cr20160418
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Santo Giorno cheese typical of the Southwestern region of Paraná, Brazil

Abstract: Santo Giorno cheese, obtained from raw milk and selected autochthonous starters, is emerging as the newest typical food product from the Southwestern region of Paraná, Brazil. The objective of this study was to evaluate the acceptance of the cheese with two ripening times of 60 and 180 days, produced in two dairy factories, testing two starters and two preservatives. Subjective sensory evaluation was applied using 129 consumers and hedonic scales for the attributes and for purchasing intent. A questionnaire in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…bulgaricus LB134. Starter culture B was composed of the same microorganisms, but the strains of Streptococcus thermophilus were different (ST98 and ST104) (Pereira et al, 2017).…”
Section: Autochthonous Starter Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…bulgaricus LB134. Starter culture B was composed of the same microorganisms, but the strains of Streptococcus thermophilus were different (ST98 and ST104) (Pereira et al, 2017).…”
Section: Autochthonous Starter Culturesmentioning
confidence: 99%
“…The cheese, denominated Santo Giorno, was manufactured at a dairy in South-West Paraná, following the production process foreseen by Pereira et al (2017). The pasteurized milk was divided in two aliquots of 1,800 liters each.…”
Section: Manufacture and Ripening Of Brazilian Regional Cheesementioning
confidence: 99%
See 1 more Smart Citation
“…bulgaricus). The acidity of fermentation was evaluated during the preparation of the Santo Giorno cheese typical of Southwestern region of Parana -Brazil, according to the methodology described by Pereira et al (2017), the results of which are showed in Figure 3. We observed that the ferments presented an excellent performance in the acidification process, generating adequate curves, characteristics of a starter culture.…”
Section: Acidifying Activity Of Lactic Bacteriamentioning
confidence: 99%
“…In Brazil, the state of Paraná is in third place in milk production. Due to the importance of the dairy sector the regional cheese called Santo Giorno emerged in the southwest mesoregion (Brandielli et al, 2020;Pereira et al, 2017). Among the factors related to cheese production, the ones that most influence the final sensory characteristics are the starter cultures used in the formulation and the ripening times (Özer & Kesenkaş, 2019).…”
Section: Introductionmentioning
confidence: 99%